Hypotrichotic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Hypotrichotic nevus seems the more appropriate term for this condition also known with the name of Brauer nevus or congenital triangular alopecia (2). It can be present at birth or become evident later on. However, once get evident it remains unchanged throughout life. Its shape is variable, rarely triangular with the base on the hairline. The parietal region is the site most frequently affected, but any area with terminal hairs also outside the scalp can be affected. The only constant feature, because present in all cases, is the structure of the hairs, which are thinner and therefore shorter and less pigmented, that is reminiscent of vellus hair, very different from the normal type of terminal hairs which are seen at their periphery. Hypotrichotic nevus is likely due to a post-zygotic mutation occurring during the fetal life and giving rise to a clone of abnormal keratinocytes.